2019
DOI: 10.1111/1346-8138.15032
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits in Japanese patients with psoriasis and psoriatic arthritis: Low intake of meat in psoriasis and high intake of vitamin A in psoriatic arthritis

Abstract: Psoriasis is characterized by T‐helper 17 cell‐dominant abnormal immunity, and hyperproliferation and abnormal differentiation of epidermal keratinocytes. Some patients are associated with arthritis. Dietary habits can modulate the pathogenesis of psoriasis. Previous studies in Western countries showed higher body mass indices, higher intake of fat and lower intake of fish or vegetables in psoriatic patients compared with the reference groups. We evaluated dietary habits in adult Japanese psoriatic patients, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
(114 reference statements)
0
27
0
Order By: Relevance
“…Psoriasis is a chronic immune‐mediated disease affecting 2%‐4% of the population in the USA and Europe, but has a lower prevalence in Asian countries according to recent epidemiological studies (Parisi et al, 2013). However, a recent epidemiological study reported that psoriasis is increasing in Japan due to a westernization of the population's diet (Yamashita et al, 2019). Pathologically, psoriasis is initially induced by dendritic cell activation, leading to IL‐23 production.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic immune‐mediated disease affecting 2%‐4% of the population in the USA and Europe, but has a lower prevalence in Asian countries according to recent epidemiological studies (Parisi et al, 2013). However, a recent epidemiological study reported that psoriasis is increasing in Japan due to a westernization of the population's diet (Yamashita et al, 2019). Pathologically, psoriasis is initially induced by dendritic cell activation, leading to IL‐23 production.…”
Section: Discussionmentioning
confidence: 99%
“…In DISH, certain factors including retinoids might stimulate mesenchymal stem cells at the periosteum or ligaments, and promote their abnormal osteoblast differentiation, leading to the hyperostosis at entheses [ 70 ]. The dietary intake of vitamin A in PSA patients was higher than that in psoriasis patients without arthritis in a Japanese study [ 71 ]. The relationship between higher vitamin A intake and the development or aggravation of PSA should further be investigated.…”
Section: The Nutrients or Food Related To Psoriasismentioning
confidence: 99%
“…The analysis of dietary habits in adult Japanese psoriasis patients revealed that they showed higher body mass indices (BMIs), higher intakes of fish/shellfish, pulses, vitamin B12, and vitamin D, and lower intake of meat, compared to those of healthy controls [ 71 ]. The results in Japanese patients are rather different from those in Western countries showing higher intake of fat and lower intake of fish though both share higher BMIs.…”
Section: The Nutrients or Food Related To Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…A Brazilian study also suggested that psoriasis patients followed an unhealthy died that predisposed them for the emergence of chronic diseases related to obesity and exacerbation of psoriatic lesions [ 71 , 73 ]. In Japan, psoriasis patients were observed to consume more fish and shellfish, leguminous plants, green and yellow vegetables, sugar and sweeteners, vitamin B12 and vitamin D, as well as less meat than healthy subjects [ 74 ]. The cited authors also reported that affected patients ingested more β-carotene and vitamin A with their diet, which evidenced radically different dietary habits of said psoriasis patients as compared to those from other parts of the world.…”
Section: Exogenous Antioxidants In the Diet Of Psoriasis Patientsmentioning
confidence: 99%